2022
DOI: 10.3389/fmicb.2022.924283
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Root Transcriptome Analysis Revealed the Role of Plant Hormones in the Colonization of an Endophytic Diazotroph

Abstract: Some sugarcane germplasms can absorb higher amounts of nitrogen via atmospheric nitrogen fixation through the bacterial diazotrophs. Most endophytic diazotrophs usually penetrate through the root, colonize inside the plant, and fix the nitrogen. To assess the plant’s bacterial association during root colonization, strain GXS16 was tagged with a plasmid-bear green fluorescent protein (GFP) gene. The results demonstrated that the strain can colonize roots all the way to the maturation zone. The strain GXS16 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In this study, the concentration of GXS16 was evident throughout the experiments, as shown by a significant increase in colonization after 6 h of inoculation. In the previous study, images taken using a fluorescent confocal microscope indicated that the tagged GXS16 penetrate the root surface and elongation zones 24 h after inoculation and carry increased nitrogenase activity [ 20 ]. We also validated that GXS16 increased plant height and dry weight by more than 15% and 20%, respectively, compared to the negative controls.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the concentration of GXS16 was evident throughout the experiments, as shown by a significant increase in colonization after 6 h of inoculation. In the previous study, images taken using a fluorescent confocal microscope indicated that the tagged GXS16 penetrate the root surface and elongation zones 24 h after inoculation and carry increased nitrogenase activity [ 20 ]. We also validated that GXS16 increased plant height and dry weight by more than 15% and 20%, respectively, compared to the negative controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Cd content of maize was significantly positively correlated with root morphology [25]. As discussed, it is possible that under Cd stress, endophytic root fungi promote the growth and elongation of root cells by regulating hormone levels, antioxidant enzymes, and other secondary metabolites in the root system [32,55,56]. Changes in physiological and metabolic processes increase root biomass and morphology, promote plant root growth, and protect plants from Cd stress [43].…”
Section: Effects and Mechanisms Of Endophytic Root Fungi In Regulatin...mentioning
confidence: 98%
“…The secondary metabolites synthesized and secreted by DSEs may also alter the inter-root microenvironment, directly affecting root growth and plant biomass [53]. Additionally, root morphological development is closely related to plant hormones, which promote the division and elongation of epidermal cells and make the host adapt better to the stressful environment [54,55]. This is attributed to the significant changes in the balance of host hormones, which slows down the restriction of plant growth by regulating the ratio of hormones of the DSE-inoculated plants [32,42].…”
Section: Effects and Mechanisms Of Endophytic Root Fungi In Regulatin...mentioning
confidence: 99%